Ultrasound-guided Versus Computed Tomography Fluoroscopy-assisted Cervical Transforaminal Steroid Injection for the Treatment of Radicular Pain in the Lower Cervical Spine: A Randomized Single-blind Controlled Noninferiority Study. Issue 2 (17th January 2023) - Yue, Li; Zheng, Shuyue; Hua, Lei; Li, Hongfu; Yang, Yuchen; Li, Juanhong; He, Liangliang
Abstract : Object: To estimate the contrast dispersion short-term clinical efficacy and safety of ultrasound (US)-guided transforaminal steroid injection (TFSI) compared with computed tomography (CT) guidance for the treatment of cervical radicular pain. Method: A total of 430 patients with cervical radicular pain from cervical herniated disk or cervical spondylosis were recruited in the randomized, single-blind, controlled, noninferiority trial. The patients were randomly assigned to receive either the US-guided or CT-guided TFSI for 1 affected cervical nerve. The dispersion pattern of contrast was monitored at the time of TFSI in both groups, using CT. Patients were assessed for pain intensity by numeric rating scale (NrS) and functional disability by Neck Disability Index (NDI) at baseline, 1 and 3 months after the intervention. Complications were also recorded. Results: The satisfactory rate of contrast distribution was respectively 92.1% in US group and 95.8% in CT group. Pain reduction and functional improvement were showed in both groups during follow-up. Statistical difference was not observed in the decrease in NRS pain scores and NDI scores between 2 groups with F =1.050, P =0.306 at 1 month and F =0.103, P =0.749 at 3 months after intervention. No permanent and severe complications were observed. Conclusions: This study demonstrated that US provided a noninferior injectate spread pattern and similar improvement of radicular pain and functional status when compared with CT-guided TFSI. US may be advantageous during this procedure because it allows visualization of critical vessels and avoids radiation exposure.